All about travel - Skull, John , Dr.; Skull, David (South Australia : Elbrook Press, 2002)
Containe information about travel began from the early civilization until the age of discovery
Early civilization - Roman empire - Medieval Age - Age of discovery - Travel by Road - Travel by Water - Travel by rail - Travel by air - Games - Quizzes
Title from container
Windows system requirement ; P166 or greater ; Windows 95/98/Me/2000/NT4 ; 32 MB RAM ; 8 x CD Rom Drive ; 16 Bit Colour Monitor
Macintosh system requirement ; System 7.1 or later ; 32 MB RAM ; 8 x CD ROM Drive ; Monitor to Thousand of colours
Keywords: Transportation -- History; Travel; Air travel; Railroad travel; Ocean travel; Travel , medieval